Dynamic tests for a Constant-Resistance-Large-Deformation bolt using a modified SHTB system. (April 2017) - He, Manchao; Li, Chen; Gong, Weili; Sousa, L.R.; Li, Shenglin
Highlights: A Constant Resistance Large Deformation (CRLD) bolt was introduced. Experiments on a Split-Hopkinson Tension Bar for CRLD bolts were performed. Numerical simulations were carried out by using different codes. Improved understanding of dynamic behavior of the CRLD bolt was achieved. Abstract: Rockbursts frequently occur in deep underground excavations in a sudden or violent ejection of blocks of rocks from excavation walls. In addition to understanding rockburst mechanisms, rockburst control is an important issue for the safety of mining operations. Bolts and anchors are efficient measures to control rockbursts and permit the efficient exploration of underground excavations in mines. As mining depths increase, anchor and bolts with larger extension and higher loading capacity are needed. This paper introduces a Constant Resistant Large Deformation (CRLD) bolt which has been developed at the State Key Laboratory for Geomechanics and Deep Underground Engineering (GDUE), in Beijing, China. Static and dynamic tests were developed for this type of bolt. Advancements in Hopkinson tests were recently developed for CRLD bolts and Split-Hopkinson Tension Bar (SHTB) experiments for these bolts were performed. This paper presents the SHTB equipment and the results obtained with one and two CRLD bolts, as well a deep analysis of the obtained results. To better understand the complex nature of the problem, numerical simulations using several softwares were done for the case of one bolt, which had the dual goal of verifying the experimental and numerical results. In addition, the numerical predictions permit one conducting analysis the behavior of the bolt while targeting the development of large deformations. Finally some relevant conclusions are drawn.